Pengembangan Media Pembelajaran Kimia Berbasis Android Untuk Penumbuhan Literasi Sains Siswa Pada Materi Reaksi Redoks Dan Elektrokimia - Harianto, Arifin; Suryati, Suryati; Khery, Yusran (Hydrogen: Jurnal Kependidikan Kimia, 2019)
The aims of this study were to produce android base chemistry learning media prototype and evaluate its elibibility and effectiveness on student science literacy growing on redox reaction and electrochemistry subject material. In form of research and development, this study was carried out by ADDIE (Analysis, Design, Development, Implementation, dan Evalution)model of instructional development. Data was collected by content and design validation questionnaire, practitioner and student respond questionnaire, and science litracy test. Data was analyzed by elegiibility percentega and categories and N-gain test. Study result showed that media design and content validity was very eleigible with 80 % of eligibility percentage. Practitioner and students respond was very eleigible with 82.22 % and 86.35 % of eligibility percentage average respectively. This media effectiveness on student literacy growing was proven by N-gain value 0.65 % with fair category. It can be concluded that android base chemistry learning media that developed was very eligible for chemisty learning application and grow student science literacy on redox reaction and electrochemistry subject material effectively.